A Study on Job Satisfaction of Employees of Automobile Companies in Nagercoil (International Journal of Food and Nutritional Sciences, 2022)
An employee gets satisfaction in his job when he or she is motivated to put greater effort to the performance. Job satisfaction is defined as the extent to which an employee feels self motivated, content and satisfied with his or her job. That is, the employee satisfaction is the feeling of pleasure, enjoyment and fulfillment that workers derive from their job. The objectives of the study are identifying the employee’s job satisfaction level of automobile companies and the impact factors. This study used the survey method using randomly selected questionnaire from the automobile companies at Nagercoil. The weighted average method is also used. It is found that employees were satisfied and identified various factors impacting on job satisfaction level and suggested to improve welfare schemes to improve job satisfaction. It is believed that the company can further bring out their workers with full satisfaction.